Analysis of the implementation of operational risk management in vegetarian culinary business - Adi Wilyanto; Angelina Julia Renaldi; Eni Valentina; Richmond Richmond; Rieza Melinda (Junal Ilmu Manajemen, 2023)
This study aims to analyze, evaluate and overcome the risk management faced by "Amicable Cafe" in developing its culinary business to achieve sales or profit targets. The method used in this research analysis is a qualitative method, namely by observing, analyzing, and interviewing related to operational activities and to find out how operational risk management is implemented by Amicable Cafe, so that it can carry out operational activities more effectively and can manage risks that are exist properly, precisely and in accordance with the level of risk faced. Based on the results of observations and interviews, operational risk can be caused by human resources or technical errors. Actions taken by Amicable Cafe to anticipate this risk by conducting direct supervision to avoid errors in the production process that cause losses. Employee control and operational systems are also in accordance with the capabilities of each employee, so that the level of effectiveness in production is always under control. Anticipation implemented by Amicable Café in avoiding risks, one example is by providing training in advance to new employees to avoid the risk of human error in café operations. This research is useful for MSME business actors, especially the culinary business, in anticipating risks that can occur in their business.